Inventory and recent changes of small glaciers on the northeast margin of the Southern Patagonia Icefield, Argentina. Issue 227 (2015) - Masiokas, M.H.; Delgado, S.; Pitte, P.; Berthier, E.; Villalba, R.; Skvarca, P.; Ruiz, L.; Ukita, J.; Yamanokuchi, T.; Tadono, T.; Marinsek, S.; Couvreux, F.; et al.
Abstract: Most glaciological studies in Argentina have focused on the large outlet glaciers of the Southern Patagonia Icefield (SPI); the numerous smaller neighboring glaciers have received significantly less attention. We present an inventory of 248 medium- to small-size glaciers (0.01–25 km 2 ) adjacent to the northeast margin of the SPI, describe their change over the period 1979–2005 and assess local and regional climatic variations in an attempt to explain the observed glacier changes. Based on an ASTER mosaic from 20 February 2005 and the ASTER Global Digital Elevation Model, we identified a total glacier area of 187.2 ± 7.4 km 2 between 600 and 2870 m a.s.l. Glaciers are largely debris-free and are concentrated in the western, more humid sector adjacent to the SPI. Using a 20 March 1979 US military intelligence Hexagon KH-9 satellite photograph, we measured a total areal reduction of ∼33.7 km 2 (15.2%) between 1979 and 2005. Ablation season temperatures from the study area have followed a regional warming trend that could partly explain the observed glacier shrinkage. Annual precipitation estimates show a gradual decrease between 1979 and 2002 that may also have contributed to the ice mass loss.